Intracranial pressure and cerebral perfusion pressure during apnoea testing for the diagnosis of brain death – an observational study. (6th May 2015) - Roth, C.; Deinsberger, W.; Kleffmann, J.; Ferbert, A.
<x xml:space="preserve">Abstract</x> Background and purpose Some authors have suggested a rise of intracranial pressure (ICP) during apnoea testing and the possibility of harm to patients. Data, however, have yet to be obtained. Methods Between October 2012 and May 2014 an observational study was performed on patients who received ICP measurements and who underwent brain death diagnosis. ICP, cerebral perfusion pressure (CPP), mean arterial blood pressure (MAP) and heart rate were recorded continuously from 15 min before the start of brain death diagnosis (baseline), during clinical examination including apnoea testing, until 15 min after this procedure. Results A total of 16 clinical examinations for brain death including apnoea testing were performed on 13 patients. All patients had primary brain lesions. Mean ICP and mean CPP during the examination were 95 ± 27.7 mmHg and 13.5 ± 20.7 mmHg, respectively. ICP and MAP showed a strong and statistically significant correlation, with Pearson's correlation coefficients of more than +0.6 or less than –0.6 in 13 of the 15 examinations. Conclusion Mean ICP even before brain death determination is increased excessively. Changes of ICP during apnoea show a clear correlation to the changes of MAP. Furthermore, CPP during the condition of brain death may not equal zero but may be positive thereby indicating some minor net influx of blood into the brain in some patients.